The safety of robot‐assisted cystectomy in patients with previous history of pelvic irradiation. (2nd April 2016) - Al Hussein Al Awamlh, Bashir; Nguyen, Daniel P.; Otto, Brandon; O'Malley, Padraic; Khan, Farehin; Brooks, Savanah; Scherr, Douglas S.
Abstract : Objective: To determine the safety of robot‐assisted cystectomy (RAC) in patients with an irradiated pelvis, by comparing perioperative complication outcomes after RAC in patients with and without a history of pelvic irradiation. Patients and Methods: In all, 252 consecutive patients underwent RAC at a tertiary referral centre from 2002 to 2013. Of all patients, 46 (18%) had a history of pelvic irradiation. Complications occurring at ≤30 days and ≤90 days of RAC were graded using the modified Clavien–Dindo classification system and additionally categorised by organ system. Baseline variables and outcomes of irradiated and non‐irradiated patients were compared using descriptive statistics. Multivariable logistic regression models were generated to test the effect of previous pelvic irradiation on complications. Results: The indications for RAC in patients with a history of pelvic irradiation were: bladder cancer (30 patients, 65%), prostate cancer (two, 4%), fistulae (five, 11%), and intractable symptoms from radiation cystitis (nine, 20%). In all, 25 (54%) irradiated and 112 (54%) non‐irradiated patients had complications at ≤90 days ( P > 0.9), of which 11 (24%) and 43 (21%) respectively had major complications ( P = 0.7). One (2%) patient with and two (1%) patients without a history of irradiation died from surgical complications ( P = 0.5). Infectious, bleeding, and gastrointestinal complications were the most common events in both groups. In multivariable analyses, a history of pelvic irradiation was not associated with a higher risk of complications. Conclusion: RAC performed by an experienced surgeon is a reasonable option in selected patients with a history of pelvic irradiation, as complication rates do not significantly differ compared with non‐irradiated patients.